2022
DOI: 10.3389/fchem.2022.841316
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of MOF-Based Photothermal Agent for Tumor Ablation

Abstract: Metal-organic frameworks (MOFs) are 3D-architecture compounds of metal ions and organic molecules with sufficient and permanent porosity, showing great potential as a versatile platform to load various functional moieties to endow the hybrid materials with specific applications. Currently, a variety of photothermal nanometals have been embedded into organic ligands for integrating the unique photothermal effects with the merits of MOFs to improve their performances for cancer therapy. In this review, we have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 115 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…4a ). Encouraged by the massive applicative potential of a photo-responsive MOF 50 , 51 , we set out to characterize the photothermal abilities of the composite and test it for different applications. First, we prepared three AuBP 850 @UIO-66 samples, as described above, with varying concentrations of AuBP 850 (1, 2, and 5 OD in the initial reaction vial) (see Supplementary Movie 1 for the 5 OD synthesis).…”
Section: Resultsmentioning
confidence: 99%
“…4a ). Encouraged by the massive applicative potential of a photo-responsive MOF 50 , 51 , we set out to characterize the photothermal abilities of the composite and test it for different applications. First, we prepared three AuBP 850 @UIO-66 samples, as described above, with varying concentrations of AuBP 850 (1, 2, and 5 OD in the initial reaction vial) (see Supplementary Movie 1 for the 5 OD synthesis).…”
Section: Resultsmentioning
confidence: 99%
“…PTT, also known as photothermal ablation, is a tumor therapy that uses photothermal agents to absorb light energy and convert it into thermal energy to ablate tumor cells. 140 Compared with chemotherapy, surgery, radiotherapy and other tumor therapies, PTT is minimally invasive and highly acceptable, and the NIR laser used in PTT is considered to be highly efficient and biosafe, 141 which has made great progress in the treatment of cancer. Recent studies have found that the combination of PTT and immunotherapy could not only achieve accurate treatment of local tumors by external light, but also effectively inhibit tumor recurrence and metastasis while ablating tumor.…”
Section: Synergistic Photo-immunotherapy Of Mn-based Npsmentioning
confidence: 99%
“…Additionally, based on their compositions and structural characteristics, MOFs-conjugate materials as photothermal agents have been classified into three groups: i) metal-doped MOFs, ii) organic-doped MOFs, and iii) polymer-coated MOFs [ 198 ]. Metal-doped MOF …”
Section: Mofs Applications In the Biomedical Fieldmentioning
confidence: 99%